1962
DOI: 10.1590/s0373-55241962000300006
|View full text |Cite
|
Sign up to set email alerts
|

Plankton studies in a mangrove environment: I first assessment of standing stock and principal ecological factors

Abstract: 1 - The quantitative relation between net phytoplankton, nanoplankton and zooplankton during the high and low tide for five days at a fixed station is reported here. The samples were collected at surface, 2 and 4 m near the Baguassu river, a typical region of mangrove environment. 2 - Measurements were made of transparence, salinity, temperature, pH, dissolved oxygen, suspended matter and dry weight (inorganic + organic). Culture of bacteria was also carried out to determine the degree of contamination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
7

Year Published

1968
1968
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 3 publications
1
15
0
7
Order By: Relevance
“…Higher values of macroinvertebrate taxa richness and total mean density occurred one month after intense rainfall that affected the natural dynamics of the river water inflow into marginal lakes. Tawari-Fufeyin et al (2008), in a study of macroinvertebrates associated with Eichhornia natans, found the highest taxa richness in rainy season, when the nutrients (nitrate and phosphate) presented the highest concentrations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher values of macroinvertebrate taxa richness and total mean density occurred one month after intense rainfall that affected the natural dynamics of the river water inflow into marginal lakes. Tawari-Fufeyin et al (2008), in a study of macroinvertebrates associated with Eichhornia natans, found the highest taxa richness in rainy season, when the nutrients (nitrate and phosphate) presented the highest concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Sorting was conducted under a stereoscopic microscope and identification was made using specialised references (Lopretto and Tell, 1995;Mugnai et al, 2010). In each of the three sampling sites of each of the six lakes, water samples were also collected at the surface close to the E. azurea stands and the following abiotic variables were determined: dissolved oxygen (Winkler method, modified by Golterman et al, 1978), pH (with a Micronal B-380 pHmeter), conductivity (with a Hach-2511 conductivimeter), total suspended solids (Teixeira and Kutner, 1962), water temperature (with a Toho Dentam ET-3 thermistor), and transparency (by a Secchi disk).…”
Section: Sampling and In-laboratory Proceduresmentioning
confidence: 99%
“…Os parâmetros da tabela de vida avaliados durante os experimentos foram: idade da primípara, idade da eclosão, tamanho da primípara, tamanho final, média de proles, total de neonatos por fêmea, fecundidade média, máximo de neonatos por prole, tempo de geração (G), taxa de crescimento (r) e taxa líquida de reprodução (R0) (Tab. (Teixeira & Kutner, 1962) e turbidez (Turbidimeter, HACH, mod. 2100p).…”
Section: Experimentos De Tabela De Vida Testando a Influência Da Qualunclassified
“…Suspended solids were determined by gravimetry, water temperature with mercury thermometer, water transparency with a Secchi disk, and photosynthetic pigments were extracted in acetone (90%) for 12 h and the concentration determined with a spectrophotometer. Suspended solids were determined according to Teixeira and Kutner (1962) and all the others according to Golterman et al (1978). Daily precipitation data during the study period (from April 26 to July 05, 2013) were obtained from the pluviometric station at Departamento de Á gua and Energia elétrica in the Municipality of Angatuba.…”
Section: Abiotic and Biotic Variablesmentioning
confidence: 99%